2020
DOI: 10.21203/rs.3.rs-68785/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The role of knee arthroscopy in managing common soft-tissue complications after total knee arthroplasty: a retrospective case series study

Abstract: Background To investigate the therapeutic efficacy of arthroscopy in 3 common soft-tissue complications, peripatellar impingement, arthrofibrosis and generalized synovitis, after total knee arthroplasty (TKA). Methods A retrospective review of patients undertaking arthroscopy for peripatellar impingement(PI), arthrofibrosis(AF) and generalized synovitis(GS) was conducted. Outcome measures included range of motion (ROM), and Knee Society Score (KSS). Intraoperative findings, surgical procedures and the existe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…24 No postarthroscopy surgical site infections or PJIs have been reported after intervention for PCS in many smaller studies 3,610,1214,16,1922,25,26 ; however, a larger and more recent cohort study reported a 4.1% rate of PJI for knee arthroscopy after TKA. 5…”
Section: Peripatellar Soft-tissue Impingementmentioning
confidence: 99%
See 4 more Smart Citations
“…24 No postarthroscopy surgical site infections or PJIs have been reported after intervention for PCS in many smaller studies 3,610,1214,16,1922,25,26 ; however, a larger and more recent cohort study reported a 4.1% rate of PJI for knee arthroscopy after TKA. 5…”
Section: Peripatellar Soft-tissue Impingementmentioning
confidence: 99%
“…An additional form of patellar fibrosis has been recently described as tethered patellar syndrome, in which fibrous bands connect the inferior pole of the patellar implant to the intercondylar notch. 5 This results in tethering of the patella that restricts patellar motion and may produce anterior knee pain.…”
mentioning
confidence: 99%
See 3 more Smart Citations